New proviverrine genus from the Early Eocene of Europe and the first phylogeny of Late Palaeocene-Middle Eocene hyaenodontidans (Mammalia) - (:unkn) unknown (My University, 2013)
A new genus and new species of Proviverrinae from the Early Eocene of Europe, Morlodon vellerei, is described. This new taxon is morphologically close to the Middle Eocene genus Matthodon, with which it shares tendencies towards a robust dentition; the two genera also share the reduction of P-1. In order to examine the phylogenetic relationships of the new genus Morlodon with Early and Middle Eocene European Proviverrinae, a phylogenetic analysis of the earliest hyaenodontidans was conducted. The taxa analysed range from Late Palaeocene to Middle Eocene and are from Africa, Asia, Europe and North America. The new phylogeny of earliest hyaenodontans clarifies the systematics of the paraphyletic assemblage Proviverrinae' and results in the recognition of five major clades. The monophyly of the Limnocyoninae and Koholiinae is supported, and two new subfamilies are erected from the Proviverrinae': Sinopaninae and Arfianinae. A new definition of the Proviverrinae is proposed: only European hyaenodontidans from Early and Middle Eocene are included in this subfamily. However, the phylogenetic relationships between the five subfamilies remain to be established. An ancestral morphotype for the Hyaenodontida is proposed in order to identify the different subfamilies. On the basis of the analysis and of data presently available, an African origin for Hyaenodontida is proposed. Hyaenodontidans are involved in the faunal dispersals that occurred around the PalaeoceneEocene (P/E) boundary. They dispersed from Africa to Asia during the Late Palaeocene (Limnocyoninae), and at the P/E boundary from Africa to Europe (Proviverrinae) and to North America through Europe (Sinopaninae and Arfianinae). Proviverrinae remain an endemic European group, whereas Sinopaninae, Limnocyoninae and Arfianinae mainly evolved in North America. Koholiinae represents the sole endemic African group. The probable African origin of the Hyaenodontida supports the diphyletism of Creodonta' and a
Keywords: African Research